Neoadjuvant therapy in pancreatic cancer: a review and update on recent trials. Issue 5 (15th September 2022) - Lo, Winifred; Zureikat, Amer
Abstract : Purpose of review: Neoadjuvant therapy (NAT) has been enthusiastically embraced for patients with operable pancreatic cancer (PDAC) in hopes of improving survival. However, the rapid integration of clinical trial data has made it difficult to discern optimal treatment strategies. The goal of this review is to summarize notable recent trials and their contributions to the field. Recent findings: The results of ESPAC-5F, NEOLAP-AIO-PAK-0113, SWOG1505, PREOPANC, HyperAcutePancreas, and ALLIANCE A021501 are reviewed in detail. These studies sequentially evaluate the different neoadjuvant treatment strategies, use of neoadjuvant chemoradiation, and immunotherapy in resectable, borderline-resectable, and locally advanced PDAC. Resection rate ranged from 24.4 to 95.7% (median 64.9%). These trials demonstrate median survival ranging from 14.9 to 41.0 months with progression-free survival ranging from 7.7 to 24.2 months. Survival results may be confounded by ability to reach resection, use of modern chemotherapy vs. gemcitabine monotherapy, and inclusion of locally advanced PDAC. Several upcoming trials will directly examine efficacy of NAT vs. adjuvant therapy, chemoradiation in the NAT setting, and molecular testing-driven chemotherapy selection. Summary: NAT is associated with improved survival for patients with borderline resectable PDAC but broader efficacy for resectable PDAC and optimal treatment strategy have yet to be defined.